Incidence of abnormalities in hatched day-old chicks of a commercial hatchery in Ogbomoso, Oyo-State, Southwest Nigeria - Ogunmoyo, O. A.; Odunsi, A.A. (Nigerian Journal of Animal Science, 2023)
Apart from optimizing hatchability, an important aim of a hatchery operator is to deliver quality day-old chicks. This trial was conducted to assess egg fertility, hatchability and incidence of day-old chicks abnormalities in a commercial hatchery. A total of 183,019 fertile eggs were collected over a six-week period and incubated. From the resultant incubations, one hundred and seventeen thousand, one hundred and sixty eight (117168) hatched day-old chicks were examined and ranked (normal or abnormal) while deformed chicks were classified as Scattered legs, Impaired feathers, Head tumor, Extra legged chicks, Disoriented beaks, Unhealed navels, Eye issues and Runts.. Data collected were analyzed using descriptive statistics. Results indicated that egg fertility and hatchability were 81.3 and 82.5% respectively at the hatchery. Abnormal chicks based on fertile eggs were 0.93%. Type of abnormality revealed higher incidence of scattered legs, runts, impaired feathers and unhealed navel which were 0.22%, 0.23%, 0.24% and 0.14%, respectively while disoriented beak, head tumour and eye issues were at a lower incidence of 0.03%, 0.05%, and 0.04% respectively. Occurrence of three or more legged chicks was 0.002%. In conclusion, chick abnormalities were at a low incidence indicating optimum hatchery and breeder stock management practices. However, there is a need for proper monitoring and evaluation of hatcheries based on actual saleable day-old chicks.